Penguatan Budaya Anti Korupsi dalam Upaya Membangun Sikap Jujur Dikalangan Pelajar SMAN 2 Boyolali: Penelitian - Rima Maya Siva Kahfi; Rifdah Rasikhah; Restu Dewa Saputra; Sri Hartini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study examines the importance of strengthening an anti-corruption culture to build honest attitudes among students of SMAN 2 Boyolali. Corruption threatens the order of national life, not only in government but also in educational environments, such as dishonesty, time corruption, and conditions in schools. This emphasizes the urgency of instilling anti-corruption values ​​​​from an early age. The research method used an interactive socialization approach with educational videos about anti-corruption education. The activity was carried out in grades 11-6 of SMAN 2 Boyolali on November 19, 2025, for 45 minutes. The process began with an interview with the guidance counselor for information on student behavior, delivery of material by the resource person, video screening, and a question and answer session. The outcome showed that students were enthusiastic about understanding the material, gaining new knowledge about honesty, responsibility, and integrity. A total of 36 students representing the class committed to implementing anti-corruption values, upholding moral honesty, and daring to reprimand dishonest friends. This study emphasizes the role of anti-corruption education in high schools as a strategy for preventing corruption and developing the character of a young generation with integrity and morals, and contributing to a culture of honesty and justice in society.